2020
DOI: 10.1785/0120200027
|View full text |Cite
|
Sign up to set email alerts
|

Stress Changes on the Garlock Fault during and after the 2019 Ridgecrest Earthquake Sequence

Abstract: ABSTRACT The recent 2019 Ridgecrest earthquake sequence in southern California jostled the seismological community by revealing a complex and cascading foreshock series that culminated in a Mw 7.1 mainshock. But the central Garlock fault, despite being located immediately south of this sequence, did not coseismically fail. Instead, the Garlock fault underwent postseismic creep and exhibited a sizeable earthquake swarm. The dynamic details of the rupture process d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These complexities pose challenges in understanding the rupture physics and regional hazard assessments. Using fault geometry assumptions based on surface traces and aftershock patterns, investigations of the Ridgecrest rupture processes and slip distributions have formed a consensus that the M w 6.4 foreshock ruptured a NE-SW fault segment, followed by the M w 7.1 mainshock occurring on the ~40 km NW-SE striking fault (Barnhart et al, 2019;Chen et al, 2020;Goldberg et al, 2020;Liu et al, 2019;Ramos et al, 2020;Ross et al, 2019;K. Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These complexities pose challenges in understanding the rupture physics and regional hazard assessments. Using fault geometry assumptions based on surface traces and aftershock patterns, investigations of the Ridgecrest rupture processes and slip distributions have formed a consensus that the M w 6.4 foreshock ruptured a NE-SW fault segment, followed by the M w 7.1 mainshock occurring on the ~40 km NW-SE striking fault (Barnhart et al, 2019;Chen et al, 2020;Goldberg et al, 2020;Liu et al, 2019;Ramos et al, 2020;Ross et al, 2019;K. Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Co-seismic activation of neighboring faults has already been reported using InSAR data (e.g., Fialko et al, 2002;Elliott et al, 2016;Wright et al, 2001). A particularly impressive example is the complex fracture pattern caused by the 2019 M w 7.1 Ridgecrest earthquake that induced slip and creep on the conjugate Garlock fault as observed by radar interferograms (Ramos et al, 2020;Xu et al, 2020). Both GPS and InSAR data testimony that the Pamir thrust system was co-seismically activated and exhibits retrograde mm-slip along tens of km.…”
Section: Static Displacementsmentioning
confidence: 72%
“…However, I have to point out that the current models don't take into account factors such as depth dependent stresses (Aochi & Tsuda, 2023), stress heterogeneity (Douilly et al., 2020; Duan & Oglesby, 2007; Wang et al., 2020) and off‐fault plasticity (Gabriel et al., 2013) that could also affect the likelihood of throughgoing rupture. This is particularly important considering that the 2019 Ridgecrest caused an increase in stress on the Garlock fault segment near the segmentation (Ramos et al., 2020). In addition, Toda and Stein (2020) showed an increase in Coulomb stress change on the section of the Garlock fault closer to the San Andreas fault.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the left-lateral Garlock fault system, which is composed of two segments separated by an extensional stepover width of 3-4 km, has high mountain ranges on its northern side and almost a flat topography on the southern side (Figure 1). This stepover is particularly important because the recent 2019 Ridgecrest 3 of 14 sequence triggered significant seismicity on the Garlock fault (Cochran et al, 2020;Shelly, 2020) and an important increase in shear stress was also observed on that segment near the segmentation (Ramos et al, 2020). Considering that the aforementioned stepover modeling studies assumed a flat topography and didn't explore whether surfaces with irregular topographies can also impact rupture propagation across fault segmentation, it is worth investigating whether topography can also affect rupture jump across fault stepovers.…”
mentioning
confidence: 99%